Analisis Kebijakan Pengupahan pada Undang-Undang Cipta Kerja (Studi Analisis: Kebijakan Pengupahan Negara Indonesia dan Australia) - Febrianna Chadijah; Roy Valiant Salomo (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
Wages are a sensitive issue in industrial relations. In addition, the wage system is an important instrument in order to create a "healthy" wage system for the business world. So that the implementation of the distribution of wage incentives is of course dependent on the policies and capabilities of the company. Indonesia has just reformed the law regarding wages through the Job Creation Law in 2020. However, the substance of the Job Creation Law, especially in the employment cluster in the wage article, almost all results in losses to workers/workers. The purpose of this study is to analyze the content of the policies contained in the Job Creation Law to be able to assess the developments that have occurred in the implementation of the policy and see its effectiveness in the wage system in Indonesia and compare it with wages in Australia. This study uses a qualitative approach, using a literature review. The results of this study indicate that there is injustice which is the problem point in the wage provisions in the Job Creation Law. Comparison of wages in the Labor Law (in PP 78 of 2015) and the Ciptaker Law (in PP 36 of 2021) is found in several indicators, namely the Basis of Wage, Wage Calculation, Minimum Wage, Bonus, Wage Structure, and Severance. For a comparison between Australia and Indonesia, among others, Australia does not determine Regional MW but only determines National MW and Award MW. Meanwhile, Indonesia sets Regional MW that differ between regions by adjusting several factors, such as the level of economic density, speed of economic rotation, and technology adoption